Polarization in Nursing—Interview Study with Nurse Leaders and Nurses - Karikumpu, Venla; Wikström, Kaisa; Nurmeksela, Anu; Hult, Marja (SAGE Publications, 2026)
Background
Polarization, defined as the division of a group into two distinct and opposing sides, has become increasingly evident in nursing. This phenomenon may negatively affect staff well-being and create significant challenges for nursing management.
Aim
To explore nurse leaders’ and nurses’ experiences and definitions of polarization in nursing practice.
Design
A qualitative study using thematic interviews analyzed through inductive content analysis.
Participants and Context
Data were collected in 2023 from nurse leaders (n = 17) through focus group interviews and nurses (n = 26) through individual interviews.
Ethical Considerations
The study adhered to ethical research principles. Institutional Review Board (IRB) approval was obtained from the relevant trade union prior to data collection. All participants provided informed consent.
Findings
Both nurse leaders and nurses perceived nursing as polarized and deeply embedded in everyday practice. Polarization manifested through diverging individuality, siloed work units, organizational structures, and pressing societal challenges. Diverging individuality was linked to personal preparedness and demographic factors, while siloed work units reflected divisions within work communities. Organizational structures were shaped by sector-specific characteristics and employment relationships. Societal challenges included differing positions on multiculturalism, geographical disparities, and other contextual factors.
Conclusions
Polarization in nursing emerges from individual, organizational, and societal dimensions. Nurse leaders primarily interpret polarization through organizational challenges, such as role conflicts and work community dynamics, whereas nurses experience it more at the individual level, for example, through reward systems. Addressing both perspectives is essential for identifying, mitigating, and preventing polarization. Understanding its multidimensional nature enables nurse leaders to implement strategies that foster inclusivity and collaboration, ultimately enhancing staff well-being, improving patient care, and strengthening organizational performance.